Laboratory studies on strength behavior of concrete added with tire derived products. (2020) - Venkatesan, G.; Saravanakumar, M.; Kapgate, Bharat P.; Rajkumar, K.
Abstract: Concrete is considered the most commonly used building material. The significant exploitation of crumb rubber waste in concrete. Reductions in strength comparatively high unevenness in durability performance are major factors preventing in concrete. This research focused on using crumb tire rubber as partial replacement of fine aggregate mixed with concrete. This Study reveals that the study of rubberized concrete with replaced control concrete. Ravage tire rubber in the form of scrap rubber was replaced for sand as fine aggregates from 0% to 15% in multiples of 3%. Investigative studies were performed with and without KOH treatment solution and the results were compared with Compressive strength, split tensile strength and flexural strength obtained in the laboratory. The test results showed that even though the compressive strength is condensed when using the crumb tires, it can meet the strength requirements partial replacement of rubber. It was observed that 6% replaced non treated and 9% of treated crumb rubber for compressive strength. For a split tensile strength optimum replace of crumb rubber as 9% for non-treated rubber and 12% for treated crumb rubber. In the flexural strength of specimens, steady raises were observed as the percentage of crumb rubber was increased. However treated and non-treated crumb rubber replacement of fine aggregate flexural strength good for up to replacement of 15% both. In these study tire crumb rubber as promising materials used in concrete to save natural mineral resources in some extent.